Psychological Distress during COVID-19 Lockdown among Dental Students and Practitioners in India: A Cross-Sectional Survey - Chakraborty, Trishnika; Subbiah, Gireesh Kumar; Damade, Yogesh (European Journal of Dentistry, 2020)
Objective In response to the coronavirus disease 2019 (COVID-19) pandemic, the Indian Government imposed a countrywide lockdown of 21 days from March 25 to April 14, 2020, which was further extended to 60 days. The sudden draconian measures changed the delivery of dental education and practice throughout the country. The study aimed to screen for depression during the COVID-19 lockdown and the factors associated with it among dental students and practitioners in highly COVID-19 infected states of India.Materials and Methods The current study is an online cross-sectional survey performed in Delhi NCR, Maharashtra, and Tamil Nadu during May 2020. The participants were recruited by convenience sampling. The main outcome measure was the screening of depression using the Patient Health Questionnaire (PHQ-9), which was categorized as mild, moderate, and severe depression. The data analysis was performed with IBM SPSS Version 23.0. A multivariable logistic regression model was fitted to identify the independent predictors of depression.Results In total, 335 dental students and practitioners participated in the survey. Among this, a significant number of the dental students (54%) and practitioners (44%) scored moderate to severe depression in terms of depression severity according to the PHQ-9 scores. Those who were screened depressed were likely to be males and younger than 30 years old. The results of correlation analysis indicated that worry about the professional growth, concerns regarding setbacks in clinical and research experiences, previous history of mental health issues, and fear of contracting COVID-19 from patients were positively related to higher depression scores in students. Moreover, for practitioners, fear of contracting COVID-19 from the patients scored higher levels of depression. The practitioners who reported less concern about their practice/job post COVID-19 lockdown and those who were able to meet their financial expenses during the lockdown were the least likely to be depressed.Conclusion The results of this study indicate a high level of depression among a significant number of dental students and practitioners. It is important to monitor and address the mental health needs of dental students and practitioners during and after the lockdown.
Keywords: depression; dentists; dental students; COVID-19; psychological impact; pandemic